1998
DOI: 10.2307/1592588
|View full text |Cite
|
Sign up to set email alerts
|

Ornithobacterium rhinotracheale Infection in Turkeys: Experimental Reproduction of the Disease

Abstract: This report details the first experimental production of clinical disease, mortality, and pathology resembling that of field infections by using Ornithobacterium rhinotracheale alone. Twenty-two-week-old male turkeys were exposed to O. rhinotracheale or lung homogenate from O. rhinotracheale-infected turkeys. Within 24 hr after inoculation, turkeys given O. rhinotracheale or lung homogenate intratracheally were depressed and coughing and had decreased feed intake. By 48 hr, several birds were coughing blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…These results corroborate with the findings of several researchers who likewise came across difficulties in producing respiratory signs in turkeys (Back et al ., 1997;De Rosa et al ., 1997;Jirjis et al ., 2004), but are in contrast with the results of other researchers. Some research groups did reproduce marked disease, occasionally evolving into death, following intratracheal and intrasaccular inoculation of ORT (Ryll et al ., 1996;Sprenger et al ., 1998). Also, van Empel et al (1996) were able to evoke clinical symptoms, albeit fairly mild (growth retardation and airsacculitis), after intra-air sacs and aerosol challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results corroborate with the findings of several researchers who likewise came across difficulties in producing respiratory signs in turkeys (Back et al ., 1997;De Rosa et al ., 1997;Jirjis et al ., 2004), but are in contrast with the results of other researchers. Some research groups did reproduce marked disease, occasionally evolving into death, following intratracheal and intrasaccular inoculation of ORT (Ryll et al ., 1996;Sprenger et al ., 1998). Also, van Empel et al (1996) were able to evoke clinical symptoms, albeit fairly mild (growth retardation and airsacculitis), after intra-air sacs and aerosol challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In all experiments that were successful in reproducing acute clinical signs in turkeys, intratracheal or intrasaccular infection was applied (Ryll et al ., 1996;Sprenger et al ., 1998) and in this way the innate defence mechanisms situated at the upper respiratory tract are possibly bypassed. Other possible factors may be host related, with the age and health status as plausible determinants, although the occurrence of the disease does not seem to be correlated to a narrow age group */not in field outbreaks, nor under experimental conditions (De Rosa et al ., 1996;Hafez, 1996;Ryll et al ., 1996;Travers, 1996;van Empel et al ., 1996;Hinz & Hafez, 1997;Sprenger et al, 1998;van Veen et al ., 2000a). Noteworthy is the observation that, in all successful experiments, conventional turkeys were used instead of SPF animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, airsacculitis, pneumonia and increased mortality were observed after aerosol, intra-tracheal, intravenous and/or intra-thoracic infection without a primer (Ryll et al, 1997a;Sprenger et al, 1998). In these studies, commercial birds were used, meaning that their microbiological and/or immunological status was uncertain, and may have contributed to the infections.…”
Section: Experimental Infectionmentioning
confidence: 99%